2012
DOI: 10.1007/s12630-012-9866-6
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane blocks for rescue analgesia following Cesarean delivery: a case series

Abstract: Purpose The role of routine transversus abdominis plane (TAP) blocks at the time of surgery for Cesarean delivery analgesia is uncertain. Previous studies have shown no additional analgesic benefit in patients receiving intrathecal morphine. We present a series of three cases where TAP blocks were used for rescue analgesia in patients who had severe post-Cesarean delivery pain after a standard spinal anesthetic containing bupivacaine 12 mg, fentanyl 10 lg, and morphine 200 lg. Clinical features All three women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
(30 reference statements)
0
17
0
2
Order By: Relevance
“…This was illustrated by a case series of TAP blocks administered for severe incisional pain after resolution of the spinal block following cesarean delivery. 258 The blocks provided excellent pain relief for 10 to 19 hours and prevented further escalation in IV opioid requirements. Isolated case reports have also described the successful application of TAP blocks for intractable incisional neuropathic pain 259 and pain from an abdominal wall hematoma 260 following cesarean delivery, as well as abdominal wall pain during pregnancy.…”
Section: The Overall Role Of Truncal Blocks In Obstetric Patientsmentioning
confidence: 99%
“…This was illustrated by a case series of TAP blocks administered for severe incisional pain after resolution of the spinal block following cesarean delivery. 258 The blocks provided excellent pain relief for 10 to 19 hours and prevented further escalation in IV opioid requirements. Isolated case reports have also described the successful application of TAP blocks for intractable incisional neuropathic pain 259 and pain from an abdominal wall hematoma 260 following cesarean delivery, as well as abdominal wall pain during pregnancy.…”
Section: The Overall Role Of Truncal Blocks In Obstetric Patientsmentioning
confidence: 99%
“…This study also revealed that there were few studies about the use of TAP block for pain relief after surgery (24). Several new studies have reported that TAP block is a safe and effective method for anesthesia in various surgeries such as cholecystectomy, laparoscopic inguinal surgery, and cesarean section; however, in order to obtain more definitive results, further investigation is needed in this area of research (11, 25). Finally, there is controversy in this field because of the complexity of the relationship between pain and analgesia induced by the TAP block.…”
Section: Discussionmentioning
confidence: 99%
“…The TAP block may also have a role to play to play in rescue analgesia post-abdominal surgery as described by Carvalho et al [34], who utilized the TAP block to manage suboptimal analgesia post-Caesarean section. Also, the TAP block is increasingly being used for analgesia outside the original scope of the block, as recently described by Gebhardt and Wu [35], who utilized the TAP block to treat abdominal wall cancer pain, and Singh et al [36], who used bilateral TAP blocks in addition to noninvasive positive pressure ventilation in the management of a patient with impending respiratory failure resulting from excessive pain following emergency laparotomy.…”
Section: Discussionmentioning
confidence: 99%